Efektivitas Latihan Lying Leg Curl untuk Meningkatkan Kekuatan Otot Tungkai pada Pemain Futsal - Dwi Suci Asriani; Sherly Mutiara (Pusat riset dan Inovasi Nasional, 2022)
This study aims to evaluate the effectiveness of lying leg curl exercises in increasing leg muscle strength among futsal players. Optimal leg muscle strength is crucial for futsal players to enhance performance and reduce the risk of injury. The research employed an experimental method with a pre-test and post-test design, involving 20 futsal players divided into two groups: the intervention group, which participated in an 8-week lying leg curl exercise program, and the control group, which did not receive any intervention. Leg muscle strength was measured using a dynamometer before and after the training program. The results showed that the intervention group experienced a significant increase in leg muscle strength compared to the control group (p < 0.05). These findings indicate that lying leg curl exercises are effective in improving leg muscle strength among futsal players, contributing to better on-field performance. This study is expected to provide insights for coaches and athletes in designing more effective training programs to enhance muscle strength.